La termografia come tecnica diagnostica non invasiva per il moderno esercizio della tutela: alcuni casi di studio - Miraglia, Francesco (Archeomatica, 2019)
The essay focuses on demonstrating the usefulness of thermography as a non-invasive diagnostic technique for restoration, especially in the analysis of historical buildings. In fact, the correct application of this technique allows us to analyze the deterioration patterns and the characteristics of the structures without damaging them. Therefore, its use is mainly recommended for interventions on cultural heritage.